Students’ Perception on the Video Used by English Teachers as Instructional Media - Khothori Khothori; Nina Suzanne (ELITE JOURNAL, 2020)
Video is one of instructional media used by English teachers to enhance students’ motivation and enthusiasm in learning English. This study aims to analyze students’ perception on the video used by English teachers in teaching English at a public islamic school in Tanah Datar, West Sumatera. This study was quantitative research involving 30 students as the sample. The instrument used was questionnaire constructed based on the theories of components of perception and advantages of video as instructional media in English learning. The questionnaire consisted of 38 items: 26 statements for cognitive aspect, 4 statements for affective aspect, and 8 statements for conative aspect of perception. To check the validity and reliability of the instrument, the researchers validated the questionnaire to 3 validators and then did try-out. The questionnaire was declared valid while the result of the try-out described that 26 items were valid and 12 items were revised, and the reliability was high (0.964) indicating that all of the items could be used to collect data. Data analysis showed that students’ perception on the video used by English teacher as an instructional media was strongly positive (66.67%) and positive (33.33%) meaning that students are welcome and feel very optimistic and highly motivated to the video used by the teachers in teaching English.